PATTERN OF SKIN DISEASES IN PATIENTS VISITING A TERTIARY CARE HEALTH FACILITY AT HYDERABAD, PAKISTAN - Memon, Khalida Naz; Soomro, Rafique Ahmed; Ansari, Mohammad Shahid (Journal of Ayub Medical College Abbottabad, 2011)
Background: The morbidity associated with skin diseases makes them an important public health problem. Very scanty literature is found on the problem which is either disease-based, community based or a specified population group-based. Objective of this study was to assess the pattern of skin diseases in patients and to determine their relation with demographic characteristics. Methods: This descriptive study was conducted at Dermatology Out-patient Department of Liaquat University Hospital, Jamshoro, Pakistan for the period from 10th January to 10th February 2008. Four hundred and eleven patients were enrolled during the study period. The study population comprised of newly diagnosed cases as well as relapsing cases presenting at the facility. The criterion for registering the patients was clinical diagnosis although few cases were supported by investigations, too. The data was collected through a pre-designed questionnaire and analysed through SPSS-12. Result: Skin problems are fairly common among children and women. In children of less than 10 years age, 82.5% visiting the facility suffer from infectious skin diseases. Among the infectious diseases, scabies is highly prevalent disease (45.5%). The majority of the patients belong to rural or slum areas (77.2%), low socio-economic strata (68.9%), and living in overcrowded families (82%). A strong association between skin infections and water inadequacy (p=0.016) was found, and scabies shows a strong statistical association with overcrowding (p=0.025). Conclusion: The skin diseases involve every age strata of our population but it is fairly common in younger age group, women, and people who do not practice hygiene. Out-reach services for the rural and slum communities and health education will give good results on prevention of skin diseases. Keywords: Skin diseases, demographic characteristics, environmental factors.